Clinical and Laboratory Characteristics of Kikuchi-Fujimoto Disease According to Age - Kim, Hye-Young; Jo, Ha Young; Kim, Seong Heon (Frontiers in Pediatrics, 2021)
Background: Little information exists regarding the differences in the clinical and laboratory characteristics of Kikuchi-Fujimoto disease (KFD) according to age. Objective: To evaluate the clinical and laboratory characteristics of KFD according to age. Methods: The relevance of sex, age, clinical features, laboratory findings, courses, and follow-up results were retrospectively evaluated in patients diagnosed with KFD at Pusan National University Hospital between 2010 and 2020. Results: Eighty patients (46 children and 34 adults) with a mean age of 21.5 ± 11.8 years (range, 3–49 years) were included in the study. Those aged 10–19 years accounted for the largest number of patients (42.5%). Among children, the male sex ratio was higher, especially for patients aged ≤ 9 years. In adults, the female sex ratio was higher, especially for patients aged 20–29 years. Fever, tenderness in the lymph node, and skin rashes were more common in children, while myalgia and weight loss were more common in adults. In children, the recurrence rate was significantly higher among boys than among girls (15.8% vs 0.0%, P=0.001); lower platelet count and higher CRP levels were observed among boys than among girls. EBV and ANA positivity rates were higher in boys than in girls. In adults, the recurrence rate was significantly higher in women than in men (18.2% vs 0.0%, P=0.005). ANA positivity rates were higher in women than in men. Conclusion: The clinical features, laboratory findings, and recurrence of KFD may differ depending on age and sex. Clinicians should be aware of this.